2017
DOI: 10.1111/ncn3.12133
|View full text |Cite
|
Sign up to set email alerts
|

Stroke recurrence among Filipino patients taking aspirin for first‐ever non‐cardioembolic ischemic stroke

Abstract: Background: Stroke is the second leading cause of death in the Philippines. There is no Filipino data on stroke recurrence rates. Aim: The present study aimed to determine the risk of recurrence for stroke, myocardial infarction and death among Filipino patients taking varying doses of aspirin with first-ever non-cardioembolic strokes, and identify factors associated with stroke recurrence. Methods: Patients aged 40-79 years with non-cardioembolic ischemic stroke within 30 days from symptom onset who were taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…29 Additionally, in 262 first-ever noncardioembolic ischemic stroke, the rate of stroke recurrence approximates what we have reported. 30 The cumulative survival rate for recurrent stroke is 92.1% in the first year and 87.6% in the second year showing a recurrent rate of 7.9% and 12.4%, respectively, in this 2-year observational study. Excellent compliance to medication and changes in lifestyle may have contributed to the low recurrence seen in this study.…”
Section: Discussionmentioning
confidence: 56%
“…29 Additionally, in 262 first-ever noncardioembolic ischemic stroke, the rate of stroke recurrence approximates what we have reported. 30 The cumulative survival rate for recurrent stroke is 92.1% in the first year and 87.6% in the second year showing a recurrent rate of 7.9% and 12.4%, respectively, in this 2-year observational study. Excellent compliance to medication and changes in lifestyle may have contributed to the low recurrence seen in this study.…”
Section: Discussionmentioning
confidence: 56%
“…In an analysis of 1025 stroke patients from 11 hospitals in the Philippines, patients who were admitted to stroke units had better outcomes than those admitted to the general neurology wards 10. For secondary prevention, a multicentre study on 262 Filipino patients taking aspirin for first-ever ischaemic stroke showed that the risk for stroke recurrence was 7.9% in the first year and 12.4% in the second year, while the risk for combined stroke, myocardial infarction and death was 8.9% in the first year and 17.9% in the second year 11. How these patients with recurrent events are managed is unclear.…”
Section: Introduction and Rationalementioning
confidence: 99%